Pembuatan Dan Penyebaran Vidio Edukasi Mengenai Tanya 5 O Dan Cara Mencuci Tangan Dengan Baik Dan Benar di Puskesmas Botania Kota Batam - Sri Hainil; Hesti Marliza, Adella (JOURNAL OF COMMUNITY DEDICATION, 2021)
Self-medication is a self-medication that is carried out by the community when they experience mild illness. Providing appropriate information can protect the public from the dangers of using drugs. And hand washing is the most important basic technique in infection prevention and control. The method used in this community service activity is to provide and disseminate information through educational videos about Tanya 5 O and washing hands properly and correctly at the Botaia Health Center Batam City through social media.